Controversials of Microscopic Colitis - Mihaly, Emese; Patai, Árpád; Tulassay, Zsolt (Frontiers in Medicine, 2021)
Microscopic colitis (MC) has become a disease with increased awareness due to the availability of new data about the pathogenesis, diagnosis and therapy of this disease. The incidence of MC is increasing, reaching the incidence of the inflammatory bowel disease (IBD) in some populations. However, some aspects of MC are still controversial. It is unknown whether the changes of microbiome play a role in the pathogenesis and what is in the background of the different subtypes of disease that can transform into each other. Is there a connection between MC and IBD or why the histological changes do not follow the clinical activity? We do not know what the etiology of the incomplete MC is, and what its natural course is. The association of MC with celiac disease is well-known- is there a common pathogenesis? The MC treatment is budesonide. Its effectiveness is high, but the relapse rate is high, as well. Why would biologics be effective in these cases when budesonide is not? This mini-review makes an attempt to summarize the data about MC and highlight that there are still unanswered questions in the pathogenesis, diagnosis and therapy of the disease, which can initiate further investigations in the future.